Computational simulation of the vestibular system using a meshless particle method - Santos, C.F. (2019)
Vestibular rehabilitation is the most used therapy in cases of unbalance diagnosis. The vertigo symptoms are commonly related with inner ear diseases, affecting 20%-30% of the world population (von Brevern & Neuhauser, 2011). Its prevalence is higher in elders. In this work, a three-dimensional model of the semi-circular canal of the vestibular system, containing the fluids that pro-mote body balance, will be used. The Smoothed-Particle Hydrodynamics (SPH) method, a meshless particle method, will be the discrete numerical technique used to simulate the fluid behaviour. In the SPH the discretization is represented by particles with constant mass (G.R. Liu & Liu, 2003). The obtained results allow to understand the behaviour of the vestibular structures during the rehabilitation manoeuvres.